MODERNISATION OF THE EDUCATION MANAGEMENT SYSTEM IN KYIV UNDER THE CONDITIONS OF IMPLEMENTING SCHOOL AUTONOMY - Hrynevych, Liliia; Lynov , Kostiantyn; Shemelynets, Ivan; Riy, Gryhoriy (The Modern Higher Education Review, 2021)
The article is devoted to the problem of the functional effectiveness of the system of educational governance in Kyiv, detection of the problems related to the establishing of the schools’ autonomy, and developing the ways of the system’s transformation. The authors have analyzed international experience in constructing an effective system of educational governance on the territorial level. In the vast majority of countries, schools are granted partial autonomy, the granting of which is accompanied by the establishment of bodies, such as, councils with supervisory and control functions consisting of representatives of the school administration, local management bodies and parents. The article demonstrated that such experience can be partly implemented in Kyiv. Several models of creating service centers for secondary schools are considered. For instance, a rational model with full financial autonomy, a balanced model with partial autonomy and outsourcing and a transitional model with the preservation of district education departments with a small staff and the establishment of separate service centers within the district or district of Kyiv. Kyiv has a two-level education governance system, in which the district educational administrations are an intermediary link between the Kyiv Educational & Research Department and the schools. In this respect, the article also analyzes legislation that grants the district education departments their mandate, regulates their functional tasks and relationships with the schools. The authors of the article propose several models of transforming the educational governance system in which the district educational administrations will take on the role of service centers.